The clinical success of ART restorations and Hall technique in primary molars: a randomized 18-month follow-up study - Esra Oz; Zuhal Kırzıoglu; Canan Kale (Restorative Dentistry & Endodontics, 2023)
ObjectivesThe aim of the study was to evaluate the clinical and radiographic success of the Hall technique (HT) and atraumatic restorative treatment (ART) restorations using high-viscosity glass-ionomer cement for the management of occlusal carious lesions in primary molars.Materials and MethodsThis randomized clinical study observed 40 children (aged 5–6 years). For each child, one tooth was treated with HT and one with ART. The primary outcome measures for HT restorations were successful, minor, and major failure rates. Clinical evaluations of ART restorations were performed according to the modified United States Public Health Service criteria during 18-month follow-up. McNemar test was used for statistical analysis.ResultsThirty of 40 (75%) participants returned for 18 months of follow-up. In the clinical evaluations of teeth that were treated with HT, the patients did not have complaints of pain or other symptoms, all crowns remained in the oral cavity, the gums were healthy, and the teeth were functional in all evaluations. At the end of the 18-month follow-up, the surface texture and marginal integrity criteria of ART restorations were recorded as 26.7% and 33.3%, respectively. In the radiographic evaluation of 30 patients treated with ART and HT, all restorations were considered successful.ConclusionsThe 18-month clinical and radiographic results after treatments applied to single-surface cavities in anxious children showed that both treatment methods were successful.